2021
DOI: 10.1002/jia2.25799
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of PrEP implementation in Kenya: adaptation of practices and contextual modifications in public HIV care clinics

Abstract: Introduction In Africa, oral pre‐exposure prophylaxis (PrEP) is largely provided via over‐burdened public HIV care clinics. Successfully incorporating PrEP services into these clinics may require adaptations to practices outlined in national implementation guidelines and modifications to routine existing service delivery. We aimed to describe adaptations made by public HIV clinics in Kenya to integrate PrEP delivery into existing services. Methods The Partners Scale‐Up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…This is consistent with findings from Zimbabwe on the benefits of multi-month PrEP dispensing to support PrEP continuation among female sex workers and was recommended recently by the World Health Organization as an approach to streamline PrEP delivery [20,30,31]. It also supports prior programmatic work from our PSUP team, which found that Kenyan clinics were moving towards efficiencies in PrEP refills with multi-month PrEP dispensing and fast-tracking stable PrEP clients through their visits even prior to the pandemic [25]. We heard about COVID-related changes to laboratory procedures during PrEP initiation and refill visits that could be maintained after the pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with findings from Zimbabwe on the benefits of multi-month PrEP dispensing to support PrEP continuation among female sex workers and was recommended recently by the World Health Organization as an approach to streamline PrEP delivery [20,30,31]. It also supports prior programmatic work from our PSUP team, which found that Kenyan clinics were moving towards efficiencies in PrEP refills with multi-month PrEP dispensing and fast-tracking stable PrEP clients through their visits even prior to the pandemic [25]. We heard about COVID-related changes to laboratory procedures during PrEP initiation and refill visits that could be maintained after the pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…Prior to the COVID‐19 pandemic, several clinics had already begun modifying how they deliver PrEP, including the adoption of multi‐month PrEP dispensing, phone calls for participants who missed visits and “fast‐tracking” stable PrEP clients (i.e. sending them directly to a clinical room without having to queue) [ 25 ], and it is possible that these clinics would have continued with these modifications in the absence of the COVID‐19 pandemic. Yet, our study found that, for some clinics, the pandemic instigated and cemented these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to PrEP uptake include low risk perception of HIV, concern of male partners, and stigma associated with HIV and PrEP [5,9,18]. In addition, the additional clinical resources and training associated with PrEP prescribing to an overburdened public health system may have diminished the initial impact of the PrEP roll-out [19]. We did observe increasing rates of PrEP use at 6-and 12-month follow-up, suggesting that national uptake of PrEP is increasing and ongoing.…”
Section: Plos Onementioning
confidence: 79%
“…the study, changes in risk perception of HIV, pill burden, lack of social support, and stigma have been described as barriers to persistence on PrEP among women in Kenya [8,17]. From a PrEP provider perspective, reduced barriers to PrEP prescribing, including reducing the frequency of clinic visits and longer refill dates, as well as sending clinic reminders may result in higher rates of persistence on PrEP [19]. Interventions to support adherence and persistence on PrEP may borrow approaches from ART adherence strategies, such as simplified PrEP delivery models (including pharmacy-deliveredwhen or other non-clinical sites), adherence clubs, and stigma reduction activities [11,19].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation